2012
DOI: 10.1111/j.1750-3639.2012.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chromosome 19q13.42 Amplification in Embryonal Brain Tumors with Ependymoblastic Multilayered Rosettes

Abstract: Recently, it was reported that ependymoblastoma and embryonal tumor with abundant neuropil and true rosettes (ETANTR) show 19q13.42 amplification at a high frequency, suggesting that these tumors may constitute a single entity. As ependymoblastic rosettes are the most prominent features in both subtypes, embryonal tumor with multilayered rosettes (ETMR) was proposed, for which 19q13.42 amplification represents a specific molecular hallmark. However, ependymoblastic rosettes are not specific to ependymoblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…In addition, Korshunov et al [4] identified 19q13.42 amplification in 93 % of ETANTRs and ependymoblastomas in a large series (41 cases), but did not identify this feature in any of 12 AT/RTs. In a previous FISH analysis of other pediatric brain tumors with ependymoblastic multilayered rosettes, Nobusawa et al [14] failed to identify the chromosome 19q13.42 amplification pattern in any cases of AT/RT. Our findings are, therefore, consistent with those of previous reports, and support the suggestion that 19q13.42 amplification is not merely related to ependymoblastic differentiation [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Korshunov et al [4] identified 19q13.42 amplification in 93 % of ETANTRs and ependymoblastomas in a large series (41 cases), but did not identify this feature in any of 12 AT/RTs. In a previous FISH analysis of other pediatric brain tumors with ependymoblastic multilayered rosettes, Nobusawa et al [14] failed to identify the chromosome 19q13.42 amplification pattern in any cases of AT/RT. Our findings are, therefore, consistent with those of previous reports, and support the suggestion that 19q13.42 amplification is not merely related to ependymoblastic differentiation [21].…”
Section: Discussionmentioning
confidence: 94%
“…Notably, in our cases, we observed that small embryonal cells had formed multilayered rosettes identical to the structures observed in ETMR cases. Nobusawa [14] suggested that in AT/RTs, multilayered rosettes (ependymoblastic rosettes) might comprise a portion of the teratoid features and could be substantially distinct from the ependymoblastic rosettes (multilayered rosettes) in ETMRs, despite their histological resemblance. Although Nobusawa also reported primitive squamous epithelia and fetal-type glands in one case, no similar structures were observed in either of our cases.…”
Section: Discussionmentioning
confidence: 98%
“…35 Finally, most recent reports demonstrated the same genetic signature in ependymoblastomas, medulloepitheliomas, and ETANTR, linking these 3 tumors genetically and clinically into a single clinicopathologic entity. 36,37 The argument in favor of this suggestion is the same genetic alteration in the same locus along with occurrence in the very young and dismal prognosis, resulting in the putative entity, embryonal tumors with multilayered rosettes (ETMRs). 37 These tumors occurred equally among male and female patients, and had a median age of 3 years at presentation.…”
Section: Embryonal Tumors With Multilayered Rosettesmentioning
confidence: 93%
“…In 2010, Paulus and Kleihues coined the term "embryonal tumor with multilayered rosettes." 24,25,29 After the original report by Pfister et al showing chromosome 19 amplification in ETMRs, other studies documented molecular abnormalities in these tumors. 2,5 In 2012, Korshunov et al proposed LIN28A overexpression as a potential biomarker for ETMRs after finding by immunohistochemistry that 100% of the ETMRs they analyzed were LIN28A positive compared with only 12% (6/50) of the AT/RTs and none of the 41 CNS PNETs (non-ETMR variants), 334 medulloblastomas, 223 anaplastic ependymomas, and 131 pediatric glioblastomas.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6][8][9][10][11][12][15][16][17][18]21,23,24,[26][27][28][29][30] In the majority of cases, including those described in the original report, the tumor was found in the supratentorial region (65 total), whereas only 35 were found in the infratentorial region-16 in the brainstem and 1 in the spinal cord. There was a slight female predominance (52%), with an average age of 28 months at initial presentation.…”
mentioning
confidence: 99%